Landmine‐detection rats: An evaluation of reinforcement procedures under simulated operational conditions. Issue 3 (27th March 2014) - Mahoney, Amanda; Lalonde, Kate; Edwards, Timothy; Cox, Christophe; Weetjens, Bart; Poling, Alan
<x xml:space="preserve">Abstract</x> Because the location of landmines is initially unknown, it is impossible to arrange differential reinforcement for accurate detection of landmines by pouched rats working on actual minefields. Therefore, provision must be made for maintenance of accurate responses by an alternative reinforcement strategy. The present experiment evaluated a procedure in which a plastic bag containing 2, 4, 6‐trinitrotoluene (TNT), the active ingredient in most landmines, was placed in contact with the ground in a disturbed area, then removed, to establish opportunities for reinforcement. Each of five rats continued to accurately detect landmines when extinction was arranged for landmine‐detection responses and detections of TNT‐contaminated locations were reinforced under a fixed‐ratio 1 schedule. The results of this translational research study suggest that the TNT‐contamination procedure is a viable option for arranging reinforcement opportunities for rats engaged in actual landmine‐detection activities and the viability of this procedure is currently being evaluated on minefields in Angola and Mozambique.